The 8p11 myeloproliferative syndrome: Genotypic and phenotypic classification and targeted therapy - Li, Taotao; Zhang, Gaoling; Zhang, Xiaoling; Lin, Hai; Liu, Qiuju (Frontiers in Oncology, 2022)
EMS(8p11 myeloproliferative syndrome, EMS) is an aggressive hematological neoplasm with/without eosinophilia caused by a rearrangement of the FGFR1 gene at 8p11-12. It was found that all cases carry chromosome abnormalities at the molecular level, not only the previously reported chromosome translocation and insertion but also a chromosome inversion. These abnormalities produced 17 FGFR1 fusion genes, of which the most common partner genes are ZNF198 on 13q11-12 and BCR of 22q11.2. The clinical manifestations can develop into AML (acute myeloid leukemia), T-LBL (T-cell lymphoblastic lymphoma), CML (chronic myeloid leukemia), CMML (chronic monomyelocytic leukemia), or mixed phenotype acute leukemia (MPAL). Most patients are resistant to traditional chemotherapy, and a minority of patients achieve long-term clinical remission after stem cell transplantation. Recently, the therapeutic effect of targeted tyrosine kinase inhibitors (such as pemigatinib and infigratinib) in 8p11 has been confirmed in vitro and clinical trials. The TKIs may become an 8p11 treatment option as an alternative to hematopoietic stem cell transplantation, which is worthy of further study.